The Dermatological Manifestations in the Coronavirus Infection COVID-19 - A. S. Dvornikov; A. A. Silin; T. A. Gaydina; V. N. Larina; P. A. Skripkina; E. V. Kiva (Архивъ внутренней медицины)
The variety of dermatological manifestations in patients with the novel coronavirus infection COVID-19, the incidence of which depends on concomitant pathology and the characteristics of drug treatment, and their characteristics are similar to those that occur with conventional viral infections is discussed. At the present time it is proposed to distinguish several groups depending on the cause and mechanism of development: angiitis of the skin; papulo-squamous rash and pink lichen; measles rash and infectious erythema; papulo-vesicular rash; toxidermia; urticarial eruptions and artifical lesions. The variety of the clinical picture of the skin manifestations of coronavirus infection requires in-depth analysis in order to interpret correctly the skin lesions and other infectious exanthema and dermatoses in patients with COVID-19.